2015
DOI: 10.1371/journal.pone.0119141
|View full text |Cite
|
Sign up to set email alerts
|

Tool Compounds Robustly Increase Turnover of an Artificial Substrate by Glucocerebrosidase in Human Brain Lysates

Abstract: Mutations in glucocerebrosidase (GBA1) cause Gaucher disease and also represent a common risk factor for Parkinson’s disease and Dementia with Lewy bodies. Recently, new tool molecules were described which can increase turnover of an artificial substrate 4MUG when incubated with mutant N370S GBA1 from human spleen. Here we show that these compounds exert a similar effect on the wild-type enzyme in a cell-free system. In addition, these tool compounds robustly increase turnover of 4MUG by GBA1 derived from huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…26 In previous studies, high concentrations of taurocholate (4−10 mM) were used to improve the signal in GCase enzyme activity assays. 16,27,28 We found that taurocholate can interfere with our assay results, which was also reported recently by Berger et al; 29 therefore, we excluded taurocholate in our screening assay. Using this approach, we discovered several different scaffolds of GCase inhibitors and activators with moderate activity.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…26 In previous studies, high concentrations of taurocholate (4−10 mM) were used to improve the signal in GCase enzyme activity assays. 16,27,28 We found that taurocholate can interfere with our assay results, which was also reported recently by Berger et al; 29 therefore, we excluded taurocholate in our screening assay. Using this approach, we discovered several different scaffolds of GCase inhibitors and activators with moderate activity.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…S1). Isofagomine selectively inhibits GBA1 at low nanomolar concentration, but not the other glucosidases, GBA2 and GBA3 (35,36). This enabled us to study whether inhibition of GBA1 activity directly affects the SC glucosyl (ceramide) composition.…”
mentioning
confidence: 99%
“…As previously shown for GCase modulators there can be a variability in potency across assays, in particular in cell‐free assays [17, 19] . Thus, we developed a cell‐based activity assay to determine the increase in human GCase activity selectively.…”
Section: Resultsmentioning
confidence: 99%
“…As previously shown for GCase modulators there can be avariability in potencyacross assays,inparticular in cell-free assays. [17,19] Thus,w ed eveloped ac ell-based activity assay to determine the increase in human GCase activity selectively. We confirmed afterwards in an orthogonal assay,w hether putative cellular activators had the capability to bind to the enzyme.…”
Section: Resultsmentioning
confidence: 99%